External Evaluation of IMF Economic Research Activities. (International Monetary Fund, 2000)
This report, commissioned by the Executive Board, was prepared by a committee of academic economists. The report assesses the appropriateness of current research activities, the quality and added value of the IMF's economic research and its utility in the IMF among its member countries and within the wider economics community. This publication also includes responses to the report by the IMF's staff, Managing Director, and Executive Board.